Pengaruh Penggunaan Garbarata Sebagai Fasilitas Penunjang Terhadap Kepuasan Penumpang Di Bandar Udara Depati Amir Pangkal Pinang - Maisyarah Azmamiyani; Zenita Kurniasari (Journal of Creative Student Research, 2023)
There are many facilities provided by airport organizers to support passenger comfort. In this case, in particular, are the facilities provided to make it easier for passengers to get to and from the plane to the arrival terminal. The use of garbarata plays an important role in services with the aim of providing comfort and satisfaction for passengers, so that passengers do not need to get off the runway and walk far from the plane to the arrival terminal or from the departure terminal to the plane. This study aims to determine whether there is an effect of the use of garbarata and how much influence it has on passenger satisfaction at Depati Amir Pangkal Pinang Airport. The population of this study was 16,727 respondents with 100 samples and data processing using SPSS (Statistical Program for Social Science). This study uses a quantitative approach based on statistical information, the reason researchers use a quantitative approach in this study is because the data that is the object of this study is the processing result of filling out the questionnaire. The results of the research that has been discussed, we can conclude that the sig value of Garbarata Facilities (X) on Passenger Satisfaction (Y) is 0.000 <0.05 so it can be concluded that Ho is rejected, then there is a significant influence between one variable of garbarata facilities (X) on passenger satisfaction variable (Y). Garbarata Facility variable contributes 0.703 or 70.3% to passenger satisfaction and the remaining 29.7% is influenced by other factors.